Argentina Country Environmental Analysis - World Bank Group (World Bank, Washington, DC, 2016)
The report is based in the diverse challenges faced by the environment and natural resource sector in Argentina, especially those relating to new challenges in the rural economy, but also by urbanization and industrial development. Steady economic growth, increasing equality, and structural economic transformations fundamentally change the features of environmental challenges – but also how they can be managed to help reverse environmental degradation, and to demonstrate that environmental sustainability, economic growth, and shared prosperity can be mutually supportive goals.